Thinking Outside the Box: A Low-cost and Pragmatic Alternative to Aerosol Boxes for Endotracheal Intubation of COVID-19 Patients. (September 2020) - Brown, Huong; Preston, David; Bhoja, Ravi
Abstract : Supplemental Digital Content is available in the text.